Testosterone versus hCG in Hypogonadotropic Hypogonadism - Comparing Clinical Effects and Evaluating Current Practice - Swashti Agarwal MD; Duong D. Tu MD; Paul F. Austin MD; Michael E. Scheurer PhD; Lefkothea P Karaviti MD, PhD (SAGE Publishing, 2020)
Background. Gonadotropin therapy is not typically used for pubertal induction in hypogonadotropic hypogonadism (HH), however, represents a promising alternative to testosterone. It can potentially lead to the maintenance of future fertility in addition to testicular growth. We compared the pubertal effects of human chorionic gonadotropin (hCG) versus testosterone in adolescent males with HH. We evaluated the current practice, among pediatric endocrinologists, to identify barriers against gonadotropin use. Methods. In this retrospective review, we compared the effect of testosterone versus hCG therapy on mean testicular volume (MTV), penile length, growth velocity, and testosterone levels. We surveyed pediatric endocrinologists at our center, using RedCap. Results . Outcomes were assessed in 52 male patients with HH (hCG, n = 4; T, n = 48) after a mean treatment duration of 13.4 (testosterone) and 13.8 months (hCG; P  = .79). Final MTV was higher with hCG (8.25 mL) than testosterone (3.4 mL; P  < .001). The groups did not differ in penile length, growth velocity, or testosterone levels. Survey results showed that more than half the providers were aware of the benefits of gonadotropins, however, 91% were uncomfortable prescribing hCG. Commonly reported barriers to prescribing hCG were lack of experience (62%) and insurance coverage concerns (52%). Conclusions. Larger testicular volume predicts faster induction of spermatogenesis. Since hCG promoted better testicular growth, compared to testosterone, it may potentially improve future fertility outcomes in HH patients. Our results identify an opportunity to improve current practice among pediatric endocrinologists worldwide and reduce barriers to prescribing gonadotropins in the adolescent population.